U.S. evolving macroeconomic dynamics: a structural investigation - Luca Benati; Haroon Mumtaz (European Central Bank (ECB), 2007)
We fit a Bayesian time-varying parameters structural VAR with stochastic volatility to the Federal Funds rate, GDP deflator inflation, real GDP growth, and the rate of growth of M2. We identify 4 shocks–monetary policy, demand non-policy, supply, and money demand–by imposing sign restrictions on the estimated reduced-form VAR on a period-by-period basis. The evolution of the monetary rule in the structural VAR accords well with narrative accounts of post-WWII U.S. economic history, with (e.g.) significant increases in the long-run coefficients on inflation and money growth around the time of the Volcker disinflation. Overall, however, our evidence points towards a dominant role played by good luck in fostering the more stable macroeconomic environment of the last two decades. First, the Great Inflation was due, to a dominant extent, to large demand non-policy shocks, and to a lower extent to supply shocks. Second, imposing either Volcker or Greenspan over the entire sample period would only have had a limited impact on the Great Inflation episode, while imposing Burns and Miller would have resulted in a counterfactual inflation path remarkably close to the actual historical one. Although the systematic component of monetary policy clearly appears to have improved over the sample period, this does not appear to have been the dominant influence in post-WWII U.S. macroeconomic dynamics.
Keywords: E32; E47; E52; E58; 330; Bayesian VARs; frequency domain; Great Inflation; identified VARs; Lucas critique; stochastic volatility; time-varying parameters; Neue klassische Makroökonomik; VAR-Modell; Geldpolitik; Theorie; USA